PENGARUH RISIKO KREDIT DAN LIKUIDITAS TERHADAP RASIO KECUKUPAN MODAL PADA PT. BPR GEBU HARAPAN - Tifany Yeldi Astuti; Hesi Eka Puteri (Adisam Publisher, 2024)
Capital Adequacy Ratio (CAR) is one of the indicators used to measure the capital adequacy of banks. Capital for banks is used to absorb losses from banking activities and as a foundation for some policies issued by banks. This study was conducted to determine (1) the effect of Non Performing Loan Ratio and Loan to Deposit Ratio on Capital Adequacy Ratio in part by PT. BPR Gebu Harapan period 2018—2022. (2) Effect on Non Performing Loan and Loan to Deposit Ratio on Capital Adequacy Ratio simultaneously on PT. BPR Gebu Harapan period 2013- 2022. The results of this study showed that (1) Partially the variables Non-Performing Loan and Loan to Deposit Ratio negatively affect the Capital Adequacy Ratio. (2) Simultaneously the variables Non Performing Loan and Loan to Deposit Ratio did not have a significant influence on the Capital Adequacy Ratio. The value of the coefficient of determination (R-Square) is 0.609. From this value it can be interpreted that the Non Performing Loan (X1) and Loan to Deposit Ratio (X2) to Capital Adequacy Ratio (Y) are 60.9%. While the remaining 39.1% were influenced by other factors that were not investigated in the study.